Utility of recombinant fusion protein ESAT6-CFP10 skin test for differential diagnosis of active tuberculosis: A prospective study - Yuan, Yuan; Xia, Lu; Wu, Qiaoyu; Liu, Xuhui; Lu, Shuihua (Frontiers in Immunology, 2023)
Background: The recombinant mycobacterium tuberculosis fusion protein ESAT6-CFP10 (EC) skin test is a new type of detection for tuberculosis infection; however, its accuracy in the differential diagnosis of active pulmonary tuberculosis remains uncertain. This study aimed to evaluate the accuracy of EC skin tests in the differential diagnosis of tuberculosis for an early real-world assessment. Methods: This prospective cohort study recruited patients suspected of active pulmonary tuberculosis in Shanghai Public Health Clinical Center from January 2021 to November 2021 for the EC skin test. The results of interferon-α release (IGRA) test completed before the skin test were collected. The sensitivity, specificity, and corresponding confidence interval of EC skin test results were calculated with the clinical diagnosis as the reference standard, and subgroup analyses were conducted. Results: A total of 349 patients received 1.0 µg/0.1 mL EC skin test and IGRA test, of which 302 were clinically diagnosed with tuberculosis, 47 had no tuberculosis, 241 were men, and 108 were women, with ages ranging from 2 to 94 years. The sensitivity and specificity of the EC skin test for patients with clinically diagnosed tuberculosis were 71.52% and 63.83%, respectively. The consistency between the EC skin test and the IGRA test is moderate (Kappa = 0.449). Conclusion: The EC skin test has limited value in the differential diagnosis of active tuberculosis. It is mainly used for the auxiliary diagnosis of tuberculosis, but insufficient for the diagnosis of active tuberculosis alone.